2008
DOI: 10.1080/03640210801944898
|View full text |Cite
|
Sign up to set email alerts
|

The Pervasiveness of 1/f Scaling in Speech Reflects the Metastable Basis of Cognition

Abstract: Human neural and behavioral activities have been reported to exhibit fractal dynamics known as 1/f noise, which is more aptly named 1/f scaling. Some argue that 1/f scaling is a general and pervasive property of the dynamical substrate from which cognitive functions are formed. Others argue that it is an idiosyncratic property of domain-specific processes. An experiment was conducted to investigate whether 1/f scaling pervades the intrinsic fluctuations of a spoken word. Ten participants each repeated the word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
131
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 42 publications
8
131
0
1
Order By: Relevance
“…101 Spectral analysis revealed that these data exhibited an unlikely but orderly dynamic relationship across the various timescales of fluctuation entailed in the signals.…”
Section: Fractal 1/f Scalingmentioning
confidence: 97%
See 1 more Smart Citation
“…101 Spectral analysis revealed that these data exhibited an unlikely but orderly dynamic relationship across the various timescales of fluctuation entailed in the signals.…”
Section: Fractal 1/f Scalingmentioning
confidence: 97%
“…This is consistent with the proposition that cognitive performance unfolds as a quasi-coordinated whole, a perspective that challenges the time-honored search for isolable components of mind. Moreover, when one considers that multiple measures of the same behavior can yield statistically independent 'streams' of 1/f scaling, 101 the alternative hypothesis that each measurement of 1/f scaling derives from a corresponding component structure entails an absurd, never-ending proliferation of ad-hoc modules. 42 Once scaling is identified in a system a natural working hypothesis is that the system may express additional forms of scaling.…”
Section: Fractal 1/f Scalingmentioning
confidence: 99%
“…Finding that both reaction times and key-contact durations display pink noise, and yet are uncorrelated and can be perturbed independently, strongly suggests that the pink noise in behavior is not the result of one, isolatable cognitive or neural component. Rather, as Kello and colleagues (2007) contend, these results, in concert with similar findings (Holden et al, 2011;Kello et al, 2008), demonstrate that fractal scaling is a general, pervasive characteristic of behavior (Beltz & Kello, 2006;Kello, 2011).…”
mentioning
confidence: 69%
“…This manipulation, however, had no effect on the scaling of the key-contact durations (mean H ≈ 0.82 in both conditions). These findings have since been corroborated by Holden, Choi, Amazeen, and Van Orden (2011), who showed that injecting random variability into the interval after a response and the beginning of the following trial affected the scaling of reaction times, but not the scaling of key-contact durations (also see Kello, Anderson, Holden & Van Orden, 2008). Finding that both reaction times and key-contact durations display pink noise, and yet are uncorrelated and can be perturbed independently, strongly suggests that the pink noise in behavior is not the result of one, isolatable cognitive or neural component.…”
mentioning
confidence: 74%
See 1 more Smart Citation